Civil Commitment for Substance Use Disorders: A National Survey of Addiction Medicine Physicians. Issue 4 (July 2021) - Jain, Abhishek; Christopher, Paul P.; Fisher, Carl Erik; Choi, C. Jean; Appelbaum, Paul S.
Abstract : Background: Civil commitment (CC) for substance use disorders (SUDs) is a legal mechanism, initiated by family members, healthcare professionals, or others, that compels individuals with substance use problems into involuntary treatment. With the recent rise of US overdose deaths, more states are considering these laws. Yet little is known about physicians' perspectives regarding CC in treating patients with SUDs. Methods: We conducted a web-based survey of American Society of Addiction Medicine (ASAM) physician members regarding their awareness of, attitudes towards, and experiences with CC for adults with SUDs. Results: One hundred sixty-five addiction physicians completed the survey; 60.7% favored, 21.5% opposed, and 17.8% were unsure regarding CC for SUDs. More than a third (38.4%) were unfamiliar with these laws and more than a quarter (28.8%) were unsure if CC for SUDs was permitted in their state. Support for CC was strongest for SUDs involving heroin (79.0%), alcohol (74.7%), and nonheroin opioids (74.7%). Those opposing CC were more likely to believe it would jeopardize patient rapport ( P < 0.001), would be ineffective for unmotivated individuals ( P < 0.001), and should only be permitted for certain substances ( P = 0.007). A majority of respondents endorsed the need for more clinician education (91.5%) and research (87.1%) on this topic. Conclusions: Although most addiction physicians in this study approve of CC for SUDs, enthusiasm for this compulsory intervention is mixed with strongest support for patients with opioid and alcohol use disorders. At the same time, many respondents are unfamiliar with these laws and most believe more education and research are needed.